Modeling Spatial Distribution of Carbon Sequestration, CO2 Absorption, and O2 Production in an Urban Area: Integrating Ground‐Based Data, Remote Sensing Technique, and GWR Model. Issue 7 (30th June 2022) - Khodakarami, Loghman; Pourmanafi, Saeid; Soffianian, Ali Reza; Lotfi, Ali
Abstract: The main purpose of this research is to model the spatial distribution of carbon sequestration, CO2 absorption, and oxygen production by trees within Isfahan city, Iran, in 2020. To quantify carbon sequestration, we accessed a sample group of trees with measured biophysical attributes. First, we calculated the biomass and carbon sequestration of a tree using the allometric and photosynthesis equations. Then, to model the spatial distribution of carbon sequestration, we used geographic weighted regression (GWR) method. In this model, the amount of calculated carbon sequestration was the dependent variable, whereas the difference between vegetation indexes of Excess Green Plant Index minus Excess Red Plant Index (ΔExGR) from the Worldview image was the independent variable. Subsequently, the spatial distribution map of CO2 absorption and oxygen production was generated. The total value of annual carbon sequestration, CO2 absorption, and O2 production was about 7704.22, 28274.502, and 20570.16 tons, respectively. The results showed that there was a strong correlation between the ΔExGR index of the canopy with calculated carbon. Integrating the ΔExGR index from a high‐resolution image with calculated carbon can contribute to developing a fast, accurate, and low‐cost method in estimating carbon sequestration and modeling its spatial distribution in urban areas. In conclusion, the results of this research can be implemented by land‐use planners to integrate urban ecosystem service concept (i.e., carbon sequestration) in planning process toward sustainability of the cities. Key Points: Contributing urban green infrastructure to mitigate climate change Inventing a geographic weighted regression model by integrating remote‐sensing data and calculated ground‐based data Mapping the spatial distribution of carbon sequestration, CO2 absorption, and O2 production within the city